2015
DOI: 10.2298/saj150706001s
|View full text |Cite
|
Sign up to set email alerts
|

Recoiling black holes in static and evolving dark matter halo potential

Abstract: We follow trajectories of kicked black holes in static and evolving dark matter halo potential. We explore both NFW and Einasto dark matter density distributions. Considered dark matter halos represent hosts of massive spiral and elliptical field galaxies. We study critical amplitude of kick velocity necessary for complete black hole ejection at various redshifts and find that ~40% lower kick velocities can remove black holes from their host haloes at z = 7 compared to z = 1. The greatest dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…(viii) Smole (2015) studied recoiling SMBHs in an evolving potential using an average halo accretion rate for the specific cases of two DM-only halos with z = 0 masses of 10 12 M and 2 · 10 13 M (their "Halo 1" and "Halo 2" respectively). Based on the assumption that gaseous dynamical friction forces are very strong near the center of the host halo, in their model if the SMBH passed through the center of the host it was assumed to instantaneously lose all momentum and stay there; they then define the "critical velocity" as the kick needed such that the SMBH never returns to pass through the host's center.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(viii) Smole (2015) studied recoiling SMBHs in an evolving potential using an average halo accretion rate for the specific cases of two DM-only halos with z = 0 masses of 10 12 M and 2 · 10 13 M (their "Halo 1" and "Halo 2" respectively). Based on the assumption that gaseous dynamical friction forces are very strong near the center of the host halo, in their model if the SMBH passed through the center of the host it was assumed to instantaneously lose all momentum and stay there; they then define the "critical velocity" as the kick needed such that the SMBH never returns to pass through the host's center.…”
Section: Discussionmentioning
confidence: 99%
“…The host will also grow, both through mergers with other halos as well as through smooth accretion from the intergalactic medium (IGM). As discussed in §1, halo growth has previously been modeled only in hydrodynamic simulations and Smole (2015). An alternative approach is to instead apply an average mass accretion rate, M h (M h , z), for which Behroozi & Silk (2015) derived a fitting function using halos in the Bolshoi and Bolshoi-Planck simulations ( Fig.…”
Section: Host Halo Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of the host halo accretion on the recoiling SMBH trajectories have been studied analytically by Smole (2015) and Choksi et al (2017). Both works have shown that host halo growth significantly influences SMBH escape velocities since SMBHs can be easily ejected from low mass galaxies at high redshifts, while halo accretion at later times makes the ejection harder.…”
Section: Introductionmentioning
confidence: 99%